2011
DOI: 10.1523/jneurosci.4314-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Cations But Not Anions Regulate the Responsiveness of Kainate Receptors

Abstract: Kainate-selective ionotropic glutamate receptors are unique among ligand-gated ion channels in their obligate requirement of external anions and cations for activation. Although it is established that the degree of kainate receptor (KAR) activation is shaped by the chemical nature of the agonist molecule, the possible complementary role of external ions has yet to be examined. Here we show that external cations but not anions regulate the responsiveness to a range of full and partial agonists acting on rat Glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…All experiments described in this study were performed on outside‐out patches excised from transfected tsA201 cells as described previously (MacLean et al 2011). Briefly, cDNAs encoding enhanced green fluorescent protein (eGFP), the GluA1 AMPAR subunit and/or stargazin were transiently transfected using the calcium phosphate method at ratios of (eGFP:GluA1:stargazin) 1:10:15 or 1:10:20 for 10–14 h. We included 10 μ m NBQX in the media to inhibit cell death.…”
Section: Methodsmentioning
confidence: 99%
“…All experiments described in this study were performed on outside‐out patches excised from transfected tsA201 cells as described previously (MacLean et al 2011). Briefly, cDNAs encoding enhanced green fluorescent protein (eGFP), the GluA1 AMPAR subunit and/or stargazin were transiently transfected using the calcium phosphate method at ratios of (eGFP:GluA1:stargazin) 1:10:15 or 1:10:20 for 10–14 h. We included 10 μ m NBQX in the media to inhibit cell death.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, the authors were later able to more directly examine agonist efficacy by studying AMPARs at the single-channel level, taking into account sub-conductance levels. These studies suggested a model whereby more efficacious agonists can better stabilize the closed conformation of a dynamic ligand binding cleft (Zhang et al 2008), an idea that has also been used to explain agonist behaviour at KARs (Maclean et al 2011). In agreement, spectroscopic measurements of the willardiine-bound GluA2 S1S2 constructs pinpointed specific residues in the cleft that undergo dynamic motions correlated with agonist potency (Fenwick & Oswald, 2008).…”
Section: The Need For a Revised Model Of Agonist Efficacymentioning
confidence: 75%
“…Accordingly, studies of the LBD dimer interface have often examined how individual residues affect the kinetics of desensitization (Horning & Mayer, 2004), with less attention paid to their role in agonist efficacy. However, other studies show that mutations along the KAR interface affect the relative efficacies of L-Glu and KA (Fleck et al 2003;Zhang et al 2006;Maclean et al 2011), in addition to the time course of desensitization.…”
Section: Agonist Efficacy Desensitization and The Lbd Dimer Interfacementioning
confidence: 99%
See 2 more Smart Citations